2022
DOI: 10.14740/jocmr4639
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Cardiorenal Syndrome Type 3: What Is Known so Far?

Abstract: Background:The concept of cardiorenal syndrome (CRS) has been established more than 10 years ago. Five distinct types of CRS have been defined. In CRS type 3, acute kidney injury (AKI) induces cardiac complications such as ventricular decompensation due to arrhythmias, myocardial ischemia, or fluid retention with or without arterial hypertension. The risk of cardiovascular events in AKI has been known for many years, even long before the introduction of the CRS concept. However, epidemiological and clinical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In addition, cardiac energy production processes were modulated, with stimulation of anaerobic ATP synthesis. In summary, the study confirmed experimental data from others, that showed a dysbalanced cardiac redox system after renal ischemia [ 47 , 48 ]. It also confirmed the concept of cardio-renal or reno-cardiac cross-talk in AKI, and thus the concept of cardiorenal syndromes in general.…”
Section: Ischemic Akisupporting
confidence: 89%
“…In addition, cardiac energy production processes were modulated, with stimulation of anaerobic ATP synthesis. In summary, the study confirmed experimental data from others, that showed a dysbalanced cardiac redox system after renal ischemia [ 47 , 48 ]. It also confirmed the concept of cardio-renal or reno-cardiac cross-talk in AKI, and thus the concept of cardiorenal syndromes in general.…”
Section: Ischemic Akisupporting
confidence: 89%
“…The concept of the cardiovascular syndrome (CRS) was introduced about 10 years ago, and classified into five categories (13,12). CRS type 1 is characterized by a rapid deterioration of cardiac function, subsequently leading to acute kidney injury (14).…”
Section: Discussionmentioning
confidence: 99%
“…16 Patschan summarized the literature on experimental studies on CRS type 3. 17 Important considerations include alterations in mitochondrial function, immune activation, oxidative stress, and effects on cardiac contractility. 17 Impaired calcium homeostasis in the hearts of animals with acute renal failure leads to decreased responses to inotropic chemicals.…”
Section: Pathogenesismentioning
confidence: 99%
“…17 Important considerations include alterations in mitochondrial function, immune activation, oxidative stress, and effects on cardiac contractility. 17 Impaired calcium homeostasis in the hearts of animals with acute renal failure leads to decreased responses to inotropic chemicals. Thirty minutes of renal ischemia caused fragmentation of cardiac mitochondria, and at 72 hours, cardiac tissue had significant apoptosis.…”
Section: Pathogenesismentioning
confidence: 99%